Phase I pharmacokinetic study of etmaben, a malonic acid derivative - P. K. Karnakova; K. K. Karnakova; T. N. Komarov; N. S. Bagaevа; M. O. Popova; D. Yu. Ivkin; O. A. Archakova; I. E. Shohin; I. A. Narkevich (Разработка и регистрация лекарственных средств)
Introduction. Etmaben is a malonic acid derivative that has shown cardiotropic activity and is a promising candidate for treating ischemic heart disease and chronic heart failure. It is currently undergoing Phase I clinical trials, and its pharmacokinetics have not yet been studied in humans.Aim. The aim of the study is to investigate the pharmacokinetics of Etmaben, film-coated tablets, 300 mg (SPCPU, Russia) in healthy volunteers after fasting administration of different doses following both single and multiple dosing over a 7-day period.Materials and methods. The open-label, non-randomized clinical trial involved 48 healthy volunteers divided into 6 cohorts. Volunteers in cohort 1 received a single dose of 600 mg of etmaben, cohort 2 received 900 mg, and cohort 3 received 1200 mg. Cohorts 4, 5, and 6 received daily doses of 600 mg, 900 mg, and 1200 mg, respectively. Plasma concentrations of etmaben were measured using high-performance liquid chromatography with tandem mass spectrometry detection. Pharmacokinetic parameters were calculated using Microsoft Excel with the Boomer extension (Department of Pharmacokinetics and Drug Metabolism, Allergan, Irvine, CA 92606, USA).Results and discussion. Pharmacokinetic parameters were calculated for 6 cohorts of 8 volunteers after single and multiple dosing of Etmaben at doses of 600, 900, and 1200 mg. The maximum plasma concentration (Cmax) of etmaben was reached on average within 0.5 h. Cmax values ranged from 2.708 ± 1.461 µg/mL to 19.871 ± 4.415 µg/mL. The maximum half-life was 0.874 ± 0.236 h, with an elimination rate constant not exceeding 1.053 ± 0.149 h–1. The mean residence time (MRT) of etmaben in plasma did not exceed 1.527 ± 0.272 h. The average volume of distribution was above 45 L, and clearance exceeded 42 L, indicating significant tissue distribution and rapid drug elimination. Due to low area under the curve values and high elimination rates, the accumulation of etmaben is minimal.Conclusion. Pharmacokinetic parameters were calculated, and averaged pharmacokinetic profiles were constructed in linear and semilogarithmic coordinates after single and multiple dosing of various etmaben doses. This study represents the first investigation of etmaben pharmacokinetics in humans, paving the way for subsequent clinical trials.